“Candidatus Propionivibrio aalborgensis”: A Novel Glycogen Accumulating Organism Abundant in Full-Scale Enhanced Biological Phosphorus Removal Plants - Albertsen, Mads; McIlroy, Simon J.; Stokholm-Bjerregaard, Mikkel; Karst, Søren M.; Nielsen, Per H. (Frontiers in Microbiology, 2016)
Enhanced biological phosphorus removal (EBPR) is widely used to remove phosphorus from wastewater. The process relies on polyphosphate accumulating organisms (PAOs) that are able to take up phosphorus in excess of what is needed for growth, whereby phosphorus can be removed from the wastewater by wasting the biomass. However, glycogen accumulating organisms (GAOs) may reduce the EBPR efficiency as they compete for substrates with PAOs, but do not store excessive amounts of polyphosphate. PAOs and GAOs are thought to be phylogenetically unrelated, with the model PAO being the betaproteobacterial “Candidatus Accumulibacter phosphatis” (Accumulibacter) and the model GAO being the gammaproteobacterial “Candidatus Competibacter phosphatis”. Here, we report the discovery of a GAO from the genus Propionivibrio, which is closely related to Accumulibacter. Propionivibrio spp. are targeted by the canonical fluorescence in situ hybridization probes used to target Accumulibacter (PAOmix), but do not store excessive amounts of polyphosphate in situ. A laboratory scale reactor, operated to enrich for PAOs, surprisingly contained co-dominant populations of Propionivibrio and Accumulibacter. Metagenomic sequencing of multiple time-points enabled recovery of near complete population genomes from both genera. Annotation of the Propionivibrio genome confirmed their potential for the GAO phenotype and a basic metabolic model is proposed for their metabolism in the EBPR environment. Using newly designed FISH probes, analyses of full-scale EBPR plants revealed that Propionivibrio is a common member of the community, constituting up to 3% of the biovolume. To avoid overestimation of Accumulibacter abundance in situ, we recommend the use of the FISH probe PAO651 instead of the commonly applied PAOmix probe set.